2018
DOI: 10.3390/cancers10100345
|View full text |Cite
|
Sign up to set email alerts
|

Castration-Resistant Prostate Cancer Refractory to Second-Generation Androgen Receptor Axis-Targeted Agents: Opportunities and Challenges

Abstract: Second-generation androgen receptor axis-targeted (ARAT) agents, namely abiraterone and enzalutamide, enable stronger blockade of the androgen receptor (AR) axis and longer survival of men with castration-resistant prostate cancer (CRPC). However, the extent of the improved survival remains insufficient and the majority of patients eventually develop resistance to these novel agents. Some patients develop resistance against ARAT treatment through mechanisms termed “complete AR independence” or “AR indifference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 92 publications
(101 reference statements)
0
18
0
Order By: Relevance
“…Guo et al (46) reported contradictory roles of Notch signaling, where it served as a tumor-promoting role in human acute lymphoblastic leukaemia or tumor-suppressive role in basal cell carcinoma. Furthermore, studies have reported synergistic positive results in PCa cells when Notch signaling inhibitors were combined with androgen deprivation therapy (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al (46) reported contradictory roles of Notch signaling, where it served as a tumor-promoting role in human acute lymphoblastic leukaemia or tumor-suppressive role in basal cell carcinoma. Furthermore, studies have reported synergistic positive results in PCa cells when Notch signaling inhibitors were combined with androgen deprivation therapy (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the majority of patients who take these new drugs experience transiently clinical and survival benefits. The disease eventually relapses and develops resistance to the next-generation agents [7]. Therefore, seeking alternative therapeutic approaches or finding better drugs to effectively treat this lethal progression are urgent needs.…”
Section: Discussionmentioning
confidence: 99%
“…Although these drugs have demonstrated substantial efficacy in patients with advanced PC, 7 non-responsiveness to therapy, development of resistance after the initial response, and disease progression remain major challenges. [8][9][10][11] Similarly, treatment with docetaxel or cabazitaxel, while providing some overall survival benefit to subjects with advanced disease is not curative. 12,13 Therefore, the development of new agents and treatment strategies for CRPC remain important goals towards addressing this unmet medical need.…”
Section: Introductionmentioning
confidence: 99%
“…A new generation of hormonal therapies, such as abiraterone, enzalutamide, and apalutamide are now available for the treatment of advanced prostate cancer (PC). Although these drugs have demonstrated substantial efficacy in patients with advanced PC, non‐responsiveness to therapy, development of resistance after the initial response, and disease progression remain major challenges . Similarly, treatment with docetaxel or cabazitaxel, while providing some overall survival benefit to subjects with advanced disease is not curative .…”
Section: Introductionmentioning
confidence: 99%